APPLICATION OF MODIFIED ZEOLITES FOR BIOETHANOL DEHYDRATION - Khaidir, Dwi Setyaningsih dan Hery Haerudin (Department of Agroindustrial Technology, Bogor Agricultural University, 2012)
ABSTRACTBioethanol dehydration was carried out using five modified natural zeolites (ZAM). This study aimed to get the best conditions of bioethanol dehydration and to determine the increasing of bioethanol grades for each modified zeolite. Bioethanol dehydration process was carried out using a batch adsorption. The content of ethanol in bioethanol increased after adsorption process for each zeolite. The increased percentages of bioethanol grades in the immersion method using ZAM1 and ZAM4 with bioethanol of 90% (v/v) were 1.22% and 1.38%, while with bioethanol of 95% the percentage were 1.27% and 1.08%, respectively. Meanwhile the resulted grades of bioethanol using purely natural zeolites with bioethanol of 90% and 95% were 0.62% and 0.72% respectively. In general, the grade of ethanol increased after the adsorption process that uses all modified zeolites samples.Keywords: bioethanol, modified zeolites, bioethanol dehydration